Performance of HDBSCAN-based Pairs Trading Strategy in Various Market Regimes : Evidence from commodity futures market - Haavisto, Joona (My University, 2023)
In the evolving landscape of financial markets, algorithmic trading strategies have risen to prominence for investors seeking optimized returns while mitigating risks. Pairs trading strategies have historically shown promise by leveraging statistical relationships between pairs of securities. However, traditional pairs trading methods have been shown to exhibit diminishing returns over extended periods. To address these challenges, this study introduces clustering algorithms with a specific focus on the HDBSCAN-based trading strategy. The primary objective is to determine whether the HDBSCAN algorithm can effectively identify meaningful clusters of futures pairs and outperform other clustering methods during a sample period from the beginning of 2000 until June 2023. The results indicate that HDBSCAN can form meaningful clusters and demonstrates strong performance with a notable Sharpe ratio of 1.4 and a Sortino ratio of 1.66. Further, HDBSCAN exhibits the lowest Maximum Drawdown (MDD) at 9.51% and the highest Calmar ratio at 0.87 among the included trading strategies. Interestingly, the no clustering benchmark is found to yield the highest returns when the risk exposure is overlooked. This study further explores the strategy's performance over time to investigate whether the strategy suffers from diminishing returns. Notably, HDBSCAN-based trading displays a Sortino ratio of 1.91 for the 2021–2023 sub-period, surpassing the overall sample period's Sortino ratio of 1.66. The performance is similar when looking at the Sharpe ratio. The strategy is further found to be rather robust to transaction costs. Regression analysis suggests that the strategy remains relatively independent of the broader market benchmarks as well as economic indicators which would imply a high degree of market neutrality. Furthermore, hidden Markov models reveal statistically significant excess returns during both bull (0.035%) and bear (0.027%) market states. The strategy is found to exhibit similar performance regardless of the prevailing market state. The similar historical VaR metrics for the bull (0.802%) and bear (0.871%) market states at a 1% confidence level further reinforces the strategy’s independence of the current market state. The relatively low-risk profile and robustness to transaction costs make the HDBSCAN-based trading strategy rather compelling. Further, the strong performance over time and independence to the broader market as well as market states reinforce the strategy as a viable option.

Finanssimarkkinoiden kehittyessä algoritmipohjaiset kaupankäyntistrategiat ovat nousseet esiin sijoittajien keskuudessa, jotka etsivät optimoituja tuottoja alhaisella riskitasolla. Parikaupankäyntistrategiat ovat historiallisesti osoittaneet lupaavuutta hyödyntämällä tilastollisia suhteita arvopaperiparien välillä. Kuitenkin perinteiset parikaupankäyntimenetelmät ovat osoittautuneet tuottavan heikentyviä tuottoja pidemmällä aikavälillä. Tämän haasteen ratkaisemiseksi tämä tutkimus esittelee klusterointialgoritmeja, keskittyen erityisesti HDBSCAN-pohjaiseen kaupankäyntistrategiaan. Tärkeimpänä tavoitteena on selvittää, voiko HDBSCAN-algoritmi tehokkaasti tunnistaa merkityksellisiä futuuriparien klustereita ja ylittää muiden klusterointimenetelmien suorituskyvyn tarkastelujakson aikana vuoden 2000 alusta kesäkuuhun 2023. Tulokset osoittavat, että HDBSCAN-pohjainen strategia muodostaa merkityksellisiä klustereita sekä osoittaa vahvaa suorituskykyä 1,4 Sharpen luvulla ja 1,66 Sortinon luvulla. Lisäksi HDBSCAN-pohjainen strategia osoittaa alhaisimman suurimman arvonlaskun (MDD) 9,51% ja korkeimman Calmarin luvun 0,87. Mielenkiintoisesti, strategia ilman klusterointia tuottaa korkeimmat tuotot, jos riskitasoa ei oteta huomioon. Opinnäytetyössä tutkitaan edelleen strategian suorituskykyä ajan myötä, jotta voimme tarkastella kärsiikö strategia heikentyvistä tuotoista. Huomionarvoisesti HDBSCAN-pohjainen kaupankäynti osoittaa 1,91 Sortinon luvun alajaksolle 2021–2023, mikä ylittää koko tarkastelujakson 1,66 Sortinon luvun. Suorituskyky on samankaltainen tarkasteltaessa Sharpen lukua. Lisäksi strategian todetaan olevan melko robusti transaktiokustannuksille. Regressioanalyysi viittaa siihen, että strategia on suhteellisen riippumaton laajemmista markkinaindikaattoreista, mikä viittaa korkeaan markkinaneutraalisuuteen. Lisäksi Markovin piilomallit paljastavat tilastollisesti merkittäviä ylituottoja sekä nousu- (0,035%) että laskumarkkinoilla (0,027%). Strategian todetaan osoittavan samankaltaista suorituskykyä riippumatta vallitsevasta markkinatilasta. Samankaltaiset historialliset VaR-mittarit nousu- (0,802%) ja laskumarkkinoilla (0,871%) 1% luottamustasolla vahvistavat edelleen strategian riippumattomuuden vallitsevasta markkinatilasta. Suhteellisen alhainen riskiprofiili ja robustius transaktiokustannuksille tekevät HDBSCAN-pohjaisesta kaupankäyntistrategiasta houkuttelevan. Lisäksi vahva suorituskyky ajan myötä ja riippumattomuus laajemmista markkinoista sekä markkinatilanteista vahvistavat strategian olevan toteuttamiskelpoinen vaihtoehto.
Keywords: HDBSCAN, unsupervised learning, pairs trading, hidden Markov model, futures